The Legal Framework of Sharia Economic Law and Its Implications on the Development of The Sharia Economic Business Sector in Indonesia - Mualim; Oyo Sunaryo Mukhlas; Burhanuddin (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2026)
The development of the Islamic economic business sector in Indonesia shows a positive trend, but it does not fully reflect the enormous demographic potential and religiosity of the Muslim community. One of the main factors influencing this condition is the existence and effectiveness of Islamic economic law (HES). This study aims to analyze the role of HES in the development of the Islamic economic business sector in Indonesia and identify challenges and opportunities for strengthening it. The research method uses a qualitative approach with a normative juridical research type through a literature review of laws and regulations, fatwas, academic literature, and national and international reports related to Islamic economics. The results show that HES plays a significant role in creating legal certainty, transaction legitimacy, and protection for parties. From an institutional perspective, fatwas from the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) serve as guidelines for sharia compliance, while the Religious Courts, through the Compilation of Islamic Economic Law (KHES), serve as the primary forum for resolving Islamic economic disputes. However, there remains a gap between the normative objectives of HES to achieve justice and prosperity and the reality of its implementation. The effectiveness of the Islamic Economics and Development Agency (HES) is still suboptimal due to regulatory fragmentation, overlapping authority between institutions, and the KHES's dominant focus on litigation. This study concludes that strengthening and integrating a more comprehensive, adaptive, and pro-business Islamic economic legal framework is essential to encourage innovation, increase competitiveness, expand public literacy, and strengthen human resource capacity. These reforms are essential prerequisites for accelerating the sustainable growth of the national Islamic economic business sector.